(untitled) (Revista de Estudios Europeos, 2026)
Throughout his twelve years of pontificate, the pope who came from the end of the world made his paternal voice heard with the authority of being not only the spiritual leader of Catholic believers, but also a moral one on a global sphere, clearly demonstrating his humanistic concern in the face of the countless challenges of his time. Regarding Europe, Francis spoke on several occasions about the internal challenges of the European Union and the role that, in his view, it could still play in the global sphere; all of that from a comprehensive approach of its complex plurality, but with an inspiring optimism for the interrelation among the member States themselves as well as between the twenty-seven and the international community as a whole. Understanding his vision of a united Europe in the 21st century is the main goal of this paper.